Quality is the Key for Emerging Issues of Population-Based Colonoscopy Screening - Jin Young Yoon; Jae Myung Cha; Yoon Tae Jeen (Korean Society of Gastrointestinal Endoscopy, 2018)
Colonoscopy is currently regarded as the gold standard and preferred method of screening for colorectal cancer (CRC). However, the benefit of colonoscopy screening may be blunted by low participation rates in population-based screening programs. Harmful effects of population-based colonoscopy screening may include complications induced by colonoscopy itself and by sedation, psychosocial distress, potential over-diagnosis, and socioeconomic burden. In addition, harmful effects of colonoscopy may increase with age and comorbidities. As the risk of adverse events in population-based colonoscopy screening may offset the benefit, the adverse events should be managed and monitored. To adopt population-based colonoscopy screening, consensus on the risks and benefits should be developed, focusing on potential harm, patient preference, socioeconomic considerations, and quality improvement of colonoscopy, as well as efficacy for CRC prevention. As suboptimal colonoscopy quality is a major pitfall of population-based screening, adequate training and regulation of screening colonoscopists should be the first step in minimizing variations in quality. Gastroenterologists should promote quality improvement, auditing, and training for colonoscopy in a population-based screening program.